ANALYSIS OF SOME PHOTO SOURCES RELATED TO THE NOGAIS - Mahsutov, Alim Kasimovic (History, Archeology and Ethnography of the Caucasus, 2022)
With the rapid spread of information technologies today, many archival materials, such as digitized old photographs and videos of representatives of the peoples of the world, in general, and the Caucasus, in particular, have become available to general public. The mentioned materials have a tremendous impact on the image and perception of the material culture of these peoples. Despite the obvious advantages of ample opportunities for the spread of scientific data, these archival and historical materials, unfortunately, are not always used correctly. For instance, on the Internet and in print media, the erroneous use of photographs depicting representatives and elements of the material culture of one people as figures and attributes of other peoples is quite common. Our study analyses four archival photographs from various sources that have appeared in scientific and popular science literature, as well as in encyclopedias, articles, websites of major state and independent media, in materials telling about the Nogai people. We aim to prevent the erroneous use of photographs that have no bearing to Nogais. To achieve this, the author attempts to verify the legitimacy of attributing the studied photographic materials to the Nogais by attracting a broad evidence base in the form of archival data, museum exhibits, works of art historians and historians, as well as a comparative analysis of available material. In the course of the study, the author has come to a sufficiently substantiated conclusion that the photographs presented in the study depict not representatives of the Nogai people, but representatives of the Balkars, Kalmyks, Cossacks and Kazakhs. The researcher of the present work urges the authors of publications about the Nogais to use photographic materials, the relevancy of which is undoubtful.
Keywords: Nogais; photography; photo source; Balkars; Kalmyks; Kazakhs; source studies; analysis; art criticism